Tied Migrant Labor Market Integration: Deconstructing Labor Market Subjectivities in South Africa - Zinatsa, Farirai; Saurombe, Musawenkosi D. (Frontiers in Psychology, 2022)
The South African labor market is characterised by a high degree inflexibility and complexity which poses significant challenges for both indigenes and migrants looking to be integrated into the labor market. These challenges are likely to be more poignant for international migrants as they face additional barriers owing to a chronically high employment rate, xenophobic sentiments and racial exclusion. For female tied migrants, gender bias, expressed through migration policies and legislation, adds yet one further layer of complexity to long term aspirations of settling in South Africa. How well tied migrants fare in the South African labor market is an important matter for consideration. Utilizing an intersectional approach and the theory of governmentality, this study sought to deconstruct the labor market subjectivities of tied migrants in South Africa. This paper used a qualitative approach, with a narrative and interpretivist research paradigm, on female tied migrants from Sub-Saharan Africa who either accompanied their husbands or followed them to South Africa in a process of family reunification. Although thirteen (13) interviews were carried out in total, as part of a broader study, the narratives of six (6) participants were included in this study, to zone in on labor market experiences. The study found that despite their high human capital, tied migrants are not likely to be well integrated into the South African labor market. Their inequality in the South African labor market was attributed to their gender, ethnicity, race, migrant status and locality and various intersection thereof through which they are subjected to informality, immobility and precarity.